The study of hydrogen production using photosynthetic bacteria rhodospirillum rubrum - Norbaya, Mat Rani (2006)
Hydrogen has been considered a potential fuel for the future since it is carbon-free and oxidized to water as a combustion product. Photoproduction of hydrogen from synthesis gas has been carried out in a batch culture. Rhodospirillum rubrum, an anaerobic photosynthetic bacterium was used in this research to catalyze water gas shift reaction which is oxidize CO and water to CO2 and hydrogen in batch fermentation. The synthesis gas (CO) was used as a source of energy along with tungsten light supplied for growth and bioconversion of the photosynthetic bacteria. The bacteria were grown under anaerobic condition in liquid media; acetate was used as a carbon source in presence of synthesis gas. The effect of different light intensity and shaking frequency on production of hydrogen were determined. The maximum hydrogen produce at intensity of 1600 lux that is 0.43 mmol H2 while shaking frequency of 300 rpm produce 0.58 mmol H2.